2006
DOI: 10.1093/jac/dkl258
|View full text |Cite
|
Sign up to set email alerts
|

Determination of gentamicin in different matrices by a new sensitive high-performance liquid chromatography-mass spectrometric method

Abstract: All these data favour the use of chromatography-mass spectrometry as a versatile technique not only suitable for gentamicin quantification loaded in drug delivery systems, but also sensitive and specific enough for in vivo and intracellular studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 12 publications
0
30
0
Order By: Relevance
“…The results here showed that there were no significant changes in the pH of the formulations. All the formulations were considered stable based on the fact that the pH of the gentamicin-lipospheres formulations were within the value given for a conventional marketed gentamicin (pH [6][7][8] which is in accordance to the literature [23] . The slight change in the pH is neither from the lipids nor the drug, because a similar change was also observed in the unloaded lipospheres (no drug).…”
Section: 1surface Morphologymentioning
confidence: 69%
See 1 more Smart Citation
“…The results here showed that there were no significant changes in the pH of the formulations. All the formulations were considered stable based on the fact that the pH of the gentamicin-lipospheres formulations were within the value given for a conventional marketed gentamicin (pH [6][7][8] which is in accordance to the literature [23] . The slight change in the pH is neither from the lipids nor the drug, because a similar change was also observed in the unloaded lipospheres (no drug).…”
Section: 1surface Morphologymentioning
confidence: 69%
“…Hence, the in vitro release of gentamicin from the formulation was studied. In vitro release was evaluated using a dialysis bag diffusion technique as described by previous researcher [23,24] . The dialysis bags were hydrated in phosphate-buffered saline, pH 7.2 overnight before the experiment.…”
Section: In Vitro Drug Release Studymentioning
confidence: 99%
“…The MIC and MBC of GEN for Brucella were 0.25 and 0.5 g/ml, respectively (14). The time during which the antibiotic concentrations exceeded the MBC in the spleen was similar over time for the two selected formulations, but GEN remained in the liver longer when it was administered in 502H microspheres (14 day) than in the 75:25H formulation (6.1 days).…”
Section: Resultsmentioning
confidence: 94%
“…Briefly, a known amount of the loaded particles was dispersed in 1 ml of 0.1 N NaOH, the samples were centrifuged (25,000 ϫ g, 15 min), and the GEN in the supernatants was quantified by HPLC-mass spectrometry (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation